2018
DOI: 10.1017/s1092852918000433
|View full text |Cite
|
Sign up to set email alerts
|

149 Deutetrabenazine for the Treatment of Tardive Dyskinesia: Results From an Open-Label, Long-Term Study

Abstract: IntroductionTardive dyskinesia (TD) is an involuntary movement disorder resulting from exposure to dopamine-receptor antagonists. In the 12-week ARM-TD and AIM-TD studies, deutetrabenazine demonstrated significant improvements in Abnormal Involuntary Movement Scale (AIMS) scores at Week 12 compared with placebo, and was generally well tolerated.ObjectiveTo evaluate the efficacy and safety of long-term deutetrabenazine therapy in patients with TD.MethodsPatients with TD who completed the ARM-TD or AIM-TD studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“… 56 In the AIM-TD trial, suicidality was reported in the 24 and 36 mg/day arms (2.7% the highest), 57 but without any difference from placebo. Also, in the long-term, OLE study, deutetrabenazine showed 42 , 58 , 59 similar adjusted incidences of AEs, compared with both the acute-phase trials and the placebo. Moreover, >90% of psychiatric AEs were mild to moderate.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“… 56 In the AIM-TD trial, suicidality was reported in the 24 and 36 mg/day arms (2.7% the highest), 57 but without any difference from placebo. Also, in the long-term, OLE study, deutetrabenazine showed 42 , 58 , 59 similar adjusted incidences of AEs, compared with both the acute-phase trials and the placebo. Moreover, >90% of psychiatric AEs were mild to moderate.…”
Section: Resultsmentioning
confidence: 77%
“…Conversely, in the ITT population, deutetrabenazine did not differ significantly from placebo regarding the Patient Global Impression of Change (PGIC) defined responder rate (12 mg/day: p =0.37, 24 mg/day: p =0.13, 36 mg/day: p =0.30) or mCDQ-24 scores (12 mg/day: p =0.66, 24 mg/day: p =0.24, 36 mg/day: p =0.12). 57 In the OLE study 58 , 59 (59 weeks, ongoing, n=304 from the ARM-TD and AIM-TD studies), all efficacy measures (continuous scores or responder rates) continued to improve from week 6 to week 54. No head to head comparison with other VMAT-2 inhibitors has been performed.…”
Section: Resultsmentioning
confidence: 99%
“…EMBASE provided a total of 115 records and upon elimination of duplicates, additional relevant abstracts regarding deutetrabenazine for the treatment of TD from congress presentations were identified . The corresponding posters from congress presentations were made available by the manufacturer, together with additional posters not routinely abstracted in EMBASE such as from presentations at the annual meetings of the American Psychiatric Association and the US Psychiatric and Mental Health Congress . An additional document from a corporate presentation by Auspex Pharmaceuticals was also accessed .…”
Section: Study Selectionmentioning
confidence: 99%
“…Additional efficacy data have been presented from an open‐label long‐term study . Patients who completed the 12‐week short‐term studies were included.…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation